Analisis Faktor Otentik Kesulitan Belajar Program Linier Berbasis Problem-Based Learning - Aris Tamarudin; Irfai fathurohman (ANARGYA: Jurnal Ilmiah Pendidikan Matematika, 2020)
The purpose of this study is twofold , first, to find out the authentic factor of learning difficulties in linear programming based on problem-based learning. Second, knowing the effectiveness of authentic assessment and problem-based learning in overcoming learning difficulties. The method in this research descriptive qualitative method. The subjects of this study were 251st grade students of SMAN 1 Bae Kudus Regency. Analysis of learning difficulties is done by interviews and measurement techniques. The research instrument uses objective tests and essays. The results of this study first, found authentic factors of linear program learning difficulties experienced by students in completing competency test questions. Second, through the use of authentic assessment and problem-based learning, each student's understanding can be clearly identified, so that action can be taken to improve and improve the quality of learning . Through learning that emphasizes the ability of each individual student to be authentically known, the skills of each individual are able to be optimal in accordance with their interests and ways of solving each problem in mathematics learning.